1989
DOI: 10.1128/jb.171.2.1106-1117.1989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of chromosomal mutations in the polysialic acid gene cluster of Escherichia coli K1

Abstract: The kps gene cluster of Escherichia coli K1 encodes functions for sialic acid synthesis, activation, polymerization, and possibly translocation qf polymer to the cell surface. The size and complexity of this membrane polysaccharide biosynthetic cluster have hindered genetic mapping and functional descriptions of the kps genes. To begin a detailed investigation of the polysialic acid synthetic mechanism, acapsular mutants were characterized to determine their probable defects in polymer synthesis. The mutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(169 citation statements)
references
References 37 publications
8
161
0
Order By: Relevance
“…Several previous attempts to overproduce and purify KpsF using commercially available expression systems failed owing to the apparent marked propensity of the KpsF fusion polypeptides to aggregate, thus preventing the use of affinity columns that depend on tertiary conformation of the fusion tag for matrix a. The n superscript refers to the null genotype of E. coli K-12 strains, which lack the kps locus (Vimr et al, 1989). b.…”
Section: Overproduction and Purification Of Kpsfmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous attempts to overproduce and purify KpsF using commercially available expression systems failed owing to the apparent marked propensity of the KpsF fusion polypeptides to aggregate, thus preventing the use of affinity columns that depend on tertiary conformation of the fusion tag for matrix a. The n superscript refers to the null genotype of E. coli K-12 strains, which lack the kps locus (Vimr et al, 1989). b.…”
Section: Overproduction and Purification Of Kpsfmentioning
confidence: 99%
“…K1 capsule mutants harbouring chromosomal kps defects are usually selected as survivors of infection by the lytic polysialic acid-specific bacteriophage K1F (Vimr and Troy, 1985a;Vimr et al, 1989). K1F binding to and hydrolysis of the polysialic acid receptor are obligatory processes for productive phage infection.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the meningococcal kpsF::aphA-3 mutant accumulated intracellular capsular polysaccharide, mutant NMB206 was lysed by freezethaw treatment or by an EDTA-HEPES method described by Moe et al (44). An E. coli strain, EV94 (kpsS::Tn10), which has been shown to accumulate intracellular capsule (45), was included as a positive control for lysis. Capsular polysaccharide released into the supernatant was quantified by ELISA.…”
Section: Mutation Of Kpsf Yielded a Defect In Capsule Expression In Tmentioning
confidence: 99%
“…1). Epistasis analysis and complementation experiments showed that polymerase activity is dependent on the structural integrity of the polysaccharide translocation and capsule assembly apparatus (9,10), suggesting the multiprotein complex diagramed below in Fig. 1.…”
mentioning
confidence: 99%